The Central American Fear of Youth - Anika Oettler (International Journal of Conflict and Violence, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false DE X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Normale Tabelle"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> It is often asserted that youth gangs and organized crime have seized Central America. For theories on contemporary Central American violence, Costa Rica, El Salvador and Nicaragua present important test cases, which demonstrate the need to differentiate the diagnosis. This paper is concerned with the social construction of violence-related national and transnational myths as a precondition for policy formulation. The notion of exploding youth violence is part of hegemonic discourses and not necessarily linked to lifeworld experiences. While discourses on youth violence differ from country to country, with varying threat levels, patterns of attention, and discursive leitmotifs, they share the monstrous image of brutal gangs (Mara Salvatrucha, Dieciocho) as the most vivid object of fear.